Impact of non-agricultural experience on new farmers’ participation in e-commerce in China: A mediation analysis based on business conditions - Liancui Wu; Haolong Yu (PLoS ONE, 2025)
In recent years, new farmers returning from non-agricultural sectors have become an important force in promoting the development of China's agricultural e-commerce. By studying the impact mechanism of non-farming work experience on their participation in e-commerce, the aim is to guide these returning new farmers to drive the development of agricultural e-commerce, improve industrial efficiency, and achieve agricultural modernization. Taking 572 new farmers returning to their hometowns in China as the target, considering the binary nature of the e-commerce participation decision (participate or not) and the continuous yet potentially censored nature of the participation degree data, the binary logistic model and Tobit model were used to analyse the influence of non-farming experience and the behaviour and degree of participation in agricultural e-commerce, and to further discuss whether there is a mediating effect of the business situation in it. The results show that: non-farming experience positively and significantly affects new farmers' e-commerce participation decision and degree, and the probability of e-commerce participation of new farmers with non-farming experience is increased by 13.5%, and the degree of their e-commerce participation is increased by 5.5%; the business situation plays a partially mediating effect; and the e-commerce participation behaviours show gender and regional heterogeneity. Based on this, suggestions are made in terms of returning home policy attraction, brand building of agricultural products, exploring foreign markets, and developing according to local conditions, so as to encourage new farmers to participate in the project of “Digital Commerce for Rural Development” and to promote rural revitalisation.